Validation analysis of a geriatric dehydration screening tool in community-dwelling and institutionalized elderly people - Rodrigues, Susana (2015)
© 2015 by the authors; licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution license (http://creativecommons.org/licenses/by/4.0/).